Nutritional status, fitness, school performance, anxiety level and health habits in primary school in the bio bÃo province of chile: a cross-sectional study (Revista horizonte, 2021)
In recent years, obesity has increased and its presence has been associated with poor physical condition, psychological problems and poor school performance. The aim of this study was to describe nutritional status, physical condition, school performance, anxiety level, and health habits in primary schoolchildren (6-7 years old). We also determined differences among overweight/obese and normal weight groups. Two studies were conducted among 1st and 2nd graders (n=276). In both studies we measured: anthropometry, physical fitness, and academic performance. In addition,in the first study, waist circumference was measured and, in the 2nd study, health habits and anxiety symptoms were obtained. Boys and girls had high levels of overweight and obesity. Those who had higher levels of BMI/age had worse physical fitness, spent less hours per week in scheduled physical activity, ate more unhealthy foods. There were no differences in academic performance. Overweight/obese girls had lower anxiety symptoms than normal weight girls. While these results shed light on current nutritional status, physical, academic and mental condition of a sample of primary school children, further studies are needed to confirm the elevated levels of obesity and overweight detected.